Effect of Giving the Active Ingredient Jellyfish Alkaloids (Bougainvillia sp.) Through Immersion Method on Changes in the Amount of Protein Plasma of Tiger Grouper (Epinephelus fuscoguttatus) Infected with Vibrio harveyi - Afifah Afifah (Central Research Institute For Agriculture, 2023)
The purpose of this study was to obtain information regarding the potency of the alkaloid active ingredient in jellyfish (Bougainvillia sp) on the immune response of tiger grouper fry infected with Vibrio harveyi bacteria through the immersion method by observing changes in appearance and the amount of plasma protein in tiger grouper infected with bacteria. V. harveyi. The research results obtained explained that the immunostimulant ingredients from jellyfish alkaloids (Bougainvillia sp.) given by immersion can stimulate non-specific and fish-specific immunity. This is characterized by an increase in the amount of protein found in fish blood plasma after administration of alkaloids. Besides that, it can also be seen that the administration of this alkaloid is able to inhibit the infection power of Vibrio harveyi. It is proven that in fish given alkaloid immunostimulants, the amount of protein that appears can be more and the protein content is also high. With a larger protein, it will be able to further stimulate non-specific immunity so that later various antibodies as specific immunity in fish will also be formed. This research ultimately concludes that jellyfish alkaloids (Bougainvillia sp) can be used as immunostimulants to inhibit bacterial attacks Vibrio harveyi in tiger grouper seeds with the optimal dose through immersion method that can be applied is 10.22 ppm. As a follow-up to the results of this study, it is suggested to carry out further research on the application of immunostimulants using jellyfish alkaloids (Bougainvillia sp.